2022
DOI: 10.1111/ans.17749
|View full text |Cite
|
Sign up to set email alerts
|

Robotic colon surgery in obese patients: a systematic review and meta‐analysis

Abstract: Background: Colon cancer resection can be technically difficult in the obese (OB) population. Robotic surgery is a promising technique but its benefits remain uncertain in OB patients. The aim of this study is to compare OB versus non-obese (NOB) patients undergoing robotic colon surgery, as well as OB patients undergoing robotic versus open or laparoscopic colonic surgery. Methods: A systematic review and meta-analysis was performed. Primary outcome measures included length of stay (LOS), surgical site infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Furthermore, the presence of a significant amount of abdominal adipose tissue limits the surgical view, particularly for laparoscopic surgery [31]. Obese individuals are more prone to cardiovascular, respiratory and metabolic conditions and are less resilient to surgical stress [32]. It has been observed that obese patients have a higher likelihood of intraoperative incidents, a slower postoperative recovery and an increased risk of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the presence of a significant amount of abdominal adipose tissue limits the surgical view, particularly for laparoscopic surgery [31]. Obese individuals are more prone to cardiovascular, respiratory and metabolic conditions and are less resilient to surgical stress [32]. It has been observed that obese patients have a higher likelihood of intraoperative incidents, a slower postoperative recovery and an increased risk of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a recognized independent risk factor for SSI [ 23 ]. A recent systematic review and meta-analysis (2022) of obese versus non-obese patients undergoing robotic colon surgery noted increased surgical site infections (SSI) in the obese patients but found no significant differences in operative time, conversion to open, or anastomotic leak rates [ 24 ]. Stoma formation in this group of patients can be technically challenging due to the thick abdominal wall and/or short mesentery.…”
Section: Discussionmentioning
confidence: 99%
“…The first, from Ngu et al 1 . examines the use of the da Vinci Xi in multi‐visceral surgery; and the second, from Wang et al 2 . presents a review of robotic surgery in the obese.…”
mentioning
confidence: 99%
“…The Wang et al . paper 2 looking at robotic surgery in the obese again demonstrates that high‐quality randomized trial data are lacking in this area, but does demonstrate robotic surgery to be safe in this challenging patient group. The aim of this study is to assess and compare the technical safety and short‐term surgical outcomes of obese patients having robotic colonic surgery, compared with non‐obese patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation